IgG4-related disease: How to place it in the spectrum of immune-mediated and rheumatologic disorders?. Issue 4 (3rd July 2020) - Borges, Tiago; Silva, Sérgio
Abstract: IgG4-related disease (IgG4-RD) is an immune-mediated fibroinflammatory disorder that results from massive expansion of polyclonal IgG4-switched B and/or plasma cells. It can virtually affect all organs and its diagnosis relies on clinical, serological and histopathological criteria. The role of autoimmunity and adaptive immune system in IgG4-RD is reflected in plasmablast differentiation, germinal center formation and IgG4 production induced by CD4+ cells expressing CD40 ligand. IgG4-RD has been considered to be a Th2/Treg-driven disorder, but follicular helper T cells are important in driving the IgG subclass switch. Prompt clinical responses to rituximab, human leukocyte antigen (HLA) associations and the presence of autoantibodies also point to the importance of adaptive immune system. However, innate immunity may induce storiform fibrosis through T-cell independent responses as a consequence of toll-like receptors activation by microbe-and damage-associated molecular patterns, while macrophages and basophils also appear to have a significant role in IgG4-RD pathogenesis. Allergic mechanisms may drive IgG4-RD, but only a subgroup has elevated IgE serum levels and peripheral eosinophilia. Finally, the 2012 revised Chapel Hill Consensus Conference nomenclature pointed IgG4-RD as a cause of large-vessel vasculitis. This review aims to discuss how to place IgG4-RD in the spectrum of immune-mediated and rheumatologic disorders.